Improving the quality of Clinical and Biomedical Research - Zavascki, Alexandre Prehn (Clinical and Biomedical Research, 2014)
We are publishing the third issue of Clinical and Biomedical Research and we are glad that the journal has been welcomed by researchers. We are still facing some challenges during this transition period. The main problems are related to manuscript editing and journal indexing, especially in terms of getting Clinical and Biomedical Research indexed in databases that previously included Revista HCPA. Many efforts have been done to solve both problems and we hope that throughout next year we will be able to fully recover some losses that occurred during this period.